Community-based ecotourism as an alternative to the development of vocational tourism - Catarina Wahyu Dyah Purbaningrum (Universitas Sarjanawiyata Tamansiswa, 2018)
The concept of ecotourism is one of the alternatives for the development of Wonosadi Forest. Ecotourism focuses on three main things: natural or ecological sustainability, economic benefits, and psychologically acceptable in social life. This study aims to determine the extent to which the concept of community-based ecotourism can be used as an alternative development of Wonosadi forest. Through the development of ecotourism, the forest wonosadi is expected to be able to: 1) build environmental and cultural awareness around the forest area wonosadi 2) reduce the negative impact of damage or environmental pollution, in this case, wonosadi forest and local culture due to ecotourism activities, 3) directly to conservation through contributions from tourist visits, 4) develop a community economy and empower local communities by creating alternative tourism products that prioritize local values and uniqueness. This study used a qualitative approach using FGD (Focus Group Discussion) method and in-depth interview, secondary data study, and literature study. The results of the analysis show that: 1) ecotourism can create business opportunities, 2) ecotourism can increase employment and 3) ecotourism can increase income while increasing equality of local income.